Child maintenance and child poverty: A comparative analysis - Mia Hakovirta (Luxembourg Income Study (LIS), 2010)
This article uses the Luxembourg Income Study datasets from circa 2004 to analyse the contribution child maintenance makes to the reduction of child poverty. The countries compared are Canada, UK, USA, Germany, Norway, Denmark, Sweden and Finland representing countries with different child maintenance schemes. Results show that the contribution that child maintenance makes in reducing overall child poverty is minimal but it can reduce child poverty among non-widowed lone mother families if maintenance is received. Countries guaranteeing child maintenance payments by the state are more effective in reducing child poverty. This article uses the Luxembourg Income Study datasets from circa 2004 to analyse the contribution child maintenance makes to the reduction of child poverty. The countries compared are Canada, UK, USA, Germany, Norway, Denmark, Sweden and Finland representing countries with different child maintenance schemes. Results show that the contribution that child maintenance makes in reducing overall child poverty is minimal but it can reduce child poverty among non-widowed lone mother families if maintenance is received. Countries guaranteeing child maintenance payments by the state are more effective in reducing child poverty.
Keywords: 330; child maintenance; child support; child poverty; comparative study; lone parents; Kinderarmut; Unterhaltsrecht; Alleinerziehende; Deutschland; Großbritannien; Kanada; Nordeuropa; USA